2014
DOI: 10.1111/clr.12338
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans aspects of novel silane system–coated titanium and zirconia implant surfaces

Abstract: Silica-coating and silanization had modified the titanium and zirconia surfaces significantly. Both the control and experimental silane primers might inhibit the biofilm formation of C. albicans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…Recent studies by Matinlinna and co-workers demonstrated that silanes were able to reduce the surface free energy of titanium surfaces [53,165], and has proven to reduce the formation of viable C. Albicans in vitro [64], although in the zirconia case the reduction of C. Albicans was also found but not due to the decrease of surface free energy as discussed in Section 2.1.2. Indeed, the reported thickness of silane was $ 50nm which could be regarded as self-assembled multilayers or ultra-thin film.…”
Section: Silanementioning
confidence: 94%
See 2 more Smart Citations
“…Recent studies by Matinlinna and co-workers demonstrated that silanes were able to reduce the surface free energy of titanium surfaces [53,165], and has proven to reduce the formation of viable C. Albicans in vitro [64], although in the zirconia case the reduction of C. Albicans was also found but not due to the decrease of surface free energy as discussed in Section 2.1.2. Indeed, the reported thickness of silane was $ 50nm which could be regarded as self-assembled multilayers or ultra-thin film.…”
Section: Silanementioning
confidence: 94%
“…A recent study by Villard et al [64] investigated the effects of a novel silane coating on adhesion characteristics of C. albicans to titanium and zirconia surfaces with similar surface roughness and morphology. The authors reported that, on grit-blasted titanium surface, the surface free energy was lowered after silane application, with a statistically higher viable colony-forming unit (CFU) counts for C. albicans on the uncoated surface with higher surface free energy.…”
Section: Surface Free Energymentioning
confidence: 99%
See 1 more Smart Citation
“…Surface characteristics can influence bond strength of resin cements [6][7][8][9][10][11][12] and glazing ceramic [13] to zirconia prosthetics, osteointegration ability [14], bacteria [15,16], and candida [17] adhesion to zirconia abutment and implant surface. Although zirconia ceramic has an acid-resistant polycrystalline structure, it has been found that zirconia can be etched by hydrofluoric acid, such that the micro-morphological surface could be created by varying the concentration and (a) Group C (control group): No further modification treatment; (b) Group GB: The zirconia samples were grit-blasting with 110 µm silica-coated alumina particles (Rocatecs, 3M ESPE, Seefeld, Germany) at a constant pressure of 3.0 bar for 15 s; (c) Group HF: The zirconia samples were then treated with 40% hydrofluoric acid (FARCO, Hong Kong, China) for 25 min at 100 • C, and then rinsed with deionized water for 60 s and air dried; and (d) Group GBHF: Zirconia surface were treated with grit-blasting with 110 µm silica-coated alumina particles (Rocatecs) at a constant pressure of 3.0 bar for 15 s, then treated with 40% hydrofluoric acid for 25 min at 100 • C, and rinsed with deionized water for 60 s and air dried.…”
Section: Introductionmentioning
confidence: 99%
“…Zirconia itself is rather hydrophobic and has a low surface free energy [3]. Its very low (approximately 5%) surface concentration of –OH groups suggests that only a very small number of reactive groups are available for chemical bonding [4,5].…”
Section: Introductionmentioning
confidence: 99%